1997
DOI: 10.1039/a607825g
|View full text |Cite
|
Sign up to set email alerts
|

A circular dichroism (CD) study of the consecutive binding of serum albumin to bilirubin. Possible implications for the bilirubin level

Abstract: Binding studies on bovine serum albumin (BSA) with bilirubin (BR) have been performed under physiological conditions using circular dichroism (CD) and electronic absorption spectroscopy (UV-VIS). Analysis of data obtained from solutions at varying BSA/BR ratios (R), overall concentrations and pH suggests the coexistence of two similarly strong complexes with 1 : 1 stoichiometry (K ass,M ca. 1 × 10 7 dm 3 mol Ϫ1 ). Further binding to BSA affords associates for which a 2 : 1 stoichiometry (K ass,B ca. 5 × 10 4 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…43 Indeed, there is little evidence that precipitates of bilirubin commonly exist in icteric plasma (or other aqueous tissues of the body; exceptions being the renal papillary tip of the Gunn rat, 44 infected bile or tissues of terminally ill patients with kernicterus 45 ). Even in Crigler-Najjar patients with very high bilirubin levels or homozygous Gunn rats there is no evidence of precipitation or aggregation of bilirubin in the circulation, observations that are consistent with circular dichroism studies on serum albumin-bilirubin binding by Lehner and colleagues 46 and their conclusion that 'even at pathophysiological total concentrations of bilirubin, the unbound portion does not exceed the solubility limit'. Case series that include several neonates with peak TSB levels of greater than 40 mg per 100 ml and as high as 59.9 mg per 100 ml, 26,47 as well as peroxidase measurements of serum B F in human newborns lend credence to this speculation.…”
supporting
confidence: 78%
“…43 Indeed, there is little evidence that precipitates of bilirubin commonly exist in icteric plasma (or other aqueous tissues of the body; exceptions being the renal papillary tip of the Gunn rat, 44 infected bile or tissues of terminally ill patients with kernicterus 45 ). Even in Crigler-Najjar patients with very high bilirubin levels or homozygous Gunn rats there is no evidence of precipitation or aggregation of bilirubin in the circulation, observations that are consistent with circular dichroism studies on serum albumin-bilirubin binding by Lehner and colleagues 46 and their conclusion that 'even at pathophysiological total concentrations of bilirubin, the unbound portion does not exceed the solubility limit'. Case series that include several neonates with peak TSB levels of greater than 40 mg per 100 ml and as high as 59.9 mg per 100 ml, 26,47 as well as peroxidase measurements of serum B F in human newborns lend credence to this speculation.…”
supporting
confidence: 78%
“…It was found that the aggregate of BR-BSA complex is clearly larger than the BR micro crystal in size at MR being 1, where the BSA concentration is much lower than that in a physiological environment, but other smaller aggregates could not be observed by a 40× objective. This result suggests that under some conditions the aggregates of the BR-BSA complex may be formed in biological interfaces and provoke diseases, 6 as well as in an unbound BR micro crystal. The BSA molecule has three domains, each having two subdomains; specialized ligand-binding cavities are located in subdomains IIA and IIIA (the high affinity site for BR resides within IIA).…”
Section: Resonance Raman Spectra Of the Aggregate Of The Br-bsa Complmentioning
confidence: 93%
“…15,16 According to the exciton chirality rule, 15,16 dipyrrinone-dipyrrinone intramolecular exciton interactions (exciton coupling) coming from either of the BR conformation of (P+) and (M-) can generate CD spectra with opposite signs. It is possible that the equilibrium racemic state is broken and an induced optical activity can be generated, [3][4][5][6][7][8] because either enantiomer of the (P+) and (M-) forms of BR binds with an external chiral protein, such as BSA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the crucial role of pigment complexation in neutralization of their toxicity, the interaction of BR with serum albumin and its model systems is one of the most studied albumin-ligand interactions. [46][47][48] VCD was used 49,50 in studies of the structural aspects of the interactions of bile pigments in model systems. Because of fast racemization of pure pigments in solution, an appropriate chiral recognition must be involved prior to a spectral study by chiroptical methods.…”
Section: Biointeractions Of Bile Pigmentsmentioning
confidence: 99%